2007
DOI: 10.1016/j.anbehav.2007.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Dog-logic: inferential reasoning in a two-way choice task and its restricted use

Abstract: Three experiments were designed to test whether adult pet dogs are able to show inferential reasoning when searching for their toy in a series of two-way choice tasks. The experimenter placed a toy under one of two identical containers and then provided some information by manipulating the covers: either both containers were lifted or just the empty or baited one. There were other trials when the experimenter not only revealed the corresponding container but manipulated also the other one without showing its c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
100
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 36 publications
12
100
1
1
Order By: Relevance
“…In certain situations, dogs' behaviour is probably driven by a motivation to satisfy ostensively signalled human imperatives in the 'here-and-now' (Topál et al 2009b) and the ostensively communicated human action demonstrations can be functionally interpreted as imperatives by dogs with the function of performing the observed action in the presence of (and 'for') the human demonstrator. In agreement with the studies showing specific sensitivity to human's communicative signals in dogs (Erdőhegyi et al 2007;Kaminski et al 2009;Riedel et al 2008), we propose that for the dog, the function of human demonstration is not (only)…”
Section: Discussionsupporting
confidence: 91%
“…In certain situations, dogs' behaviour is probably driven by a motivation to satisfy ostensively signalled human imperatives in the 'here-and-now' (Topál et al 2009b) and the ostensively communicated human action demonstrations can be functionally interpreted as imperatives by dogs with the function of performing the observed action in the presence of (and 'for') the human demonstrator. In agreement with the studies showing specific sensitivity to human's communicative signals in dogs (Erdőhegyi et al 2007;Kaminski et al 2009;Riedel et al 2008), we propose that for the dog, the function of human demonstration is not (only)…”
Section: Discussionsupporting
confidence: 91%
“…Several studies with domestic dogs support this assumption (Szetei et al, 2003; Erdõhegyi et al, 2007; and see also Topál et al, 2009) in which researchers showed that some aspect of dogs’ cognitive skills can be masked by using human social communicative cues and thus false conclusions can be drawn about their cognitive abilities. Utilization of unfamiliar moving inanimate objects (robots) as social partners can be useful in such investigations especially if the physical appearance of the robot does not resemble the embodiment of the subject species or any heterospecifics with whom they engage in daily interactions (Gergely et al, 2013).…”
Section: Discussionmentioning
confidence: 97%
“…If they reason by exclusion, they should use the information about where the reward is not to exclude that location, and instead select the other cup. Individuals of numerous animal species have been found to successfully reason by exclusion in this procedure, including great apes (Call, 2004; Hill, Collier-Baker, & Suddendorf, 2011), siamangs (Hill et al, 2011), olive baboons (Schmitt & Fischer, 2009), capuchin monkeys (Heimbauer, Antworth, & Owren 2012; Paukner, Huntsberry, & Suomi, 2009; Sabbatini & Visalberghi, 2008), lemurs (Maille & Roeder, 2012), dogs (Erdohegyi, Topal, Viranyi, & Miklosi, 2007), ravens (Schloegl et al, 2009), carrion crows (Mikolasch, Kotrschal, & Schloegl, 2012), and African grey parrots (Pepperberg et al, 2013; Schloegl et al, 2012). Three-, 4- and 5-year-old children also readily solve the cups task (Hill, Collier-Baker, & Suddendorf, 2012), and 24- and 27-month-olds succeed on a version in which the information is conveyed verbally (Austin, Theakson, Lieven, & Tomasello, 2014).…”
Section: Introductionmentioning
confidence: 99%